PENGEMBANGAN LKPD BERBASIS DISCOVERY LEARNING PADA TEMA PENGALAMANKU KELAS I SEKOLAH DASAR - Rani Ravika Dewi; Nurmairina, Nurmairina (Jurnal Cakrawala Ilmiah, 2024)
This development research aims to develop a product worksheet based on Discovery Learning with the theme "My Experience" which is suitable for use in the learning process. This research is a type of development research (Research and Development) using the ADDIE development model. In this study, researchers carried out the ADDIE development model only up to the development stage. The instrument used to collect data was a questionnaire or questionnaire given to several expert validators, namely LKPD expert validators, material expert validators and learning expert validators. Based on the validation results from the LKPD expert validator, a score of 82 was obtained with the "Very Eligible" criteria. From the results of the material expert validation, a score of 90 was obtained with the criteria of "Very Eligible". From the results of the validation of learning experts, a score of 95 was obtained with the criteria of "Very Eligible". The average score from the results of the assessment of the three expert validators obtained a score of 89. According to the scoring criteria, it can be said that the LKPD based on Discovery Learning "My Experience" which was developed is "Very Eligible" for use in the learning process.